THE IMPACT OF WORK-LIFE BALANCE AND WORKLOAD ON EMPLOYEE PRODUCTIVITY: EVIDENCE FROM JNE EXPRESS COMPANY INDONESIA - Fithri, Aliya Maulidya; Turyandi, Itto; Triaji, Ermi (KarismaPro, 2025)
Work-life balance and workload management have emerged as critical factors influencing employee productivity in the modern logistics industry. This study examined the effects of work-life balance and workload on employee productivity at JNE Express Company's Gedebage branch in Bandung, Indonesia. A quantitative approach utilizing path analysis was employed with 175 employees selected through proportionate random sampling from a population of 310 workers. Data collection employed validated questionnaires measuring work-life balance dimensions including work interference with personal life, personal life interference with work, personal life enhancement of work, and work enhancement of personal life. Workload was assessed through job conditions, working time utilization, and target achievement dimensions. Employee productivity was evaluated across five dimensions: resource utilization efficiency, work quality, planning and management effectiveness, innovation and development, and work-life balance maintenance. Path analysis revealed that work-life balance demonstrated a significant positive effect on employee productivity (β = 0.466, p 0.001) with a total influence of 35.52%. Workload similarly showed significant positive effects on productivity (β = 0.456, p 0.001) contributing 34.6% to overall productivity variance. The combined model explained 70.1% of productivity variance (R² = 0.701), indicating strong predictive validity. These findings suggest that effective work-life balance policies and optimal workload distribution represent strategic human resource management interventions for enhancing organizational performance in logistics operations. The research contributes empirical evidence supporting the positive relationship between work-life balance, workload management, and productivity outcomes in Indonesian logistics contexts.